The predictive validity of academic performance of bs criminology graduates at solis institute of technology, bulan, sorsogon in passing the licensure examination for criminologist - Barreda, Manilyn B. (San Miguel, Iriga City: University of Saint Anthony, 2019)
The predictive validity of academic performance of bs criminology graduates at solis institute of technology, bulan, sorsogon in passing the licensure examination for criminologist.
Includes bibliographical references.
English